Examining the Relationship between Social Media Use Intensity, Content Quality, Self-Confidence, and Entrepreneurial Intention - Bekti Utomo; Tri Wisudawati; Betania Kartika Muflih; Salim Diarra (Indonesian Journal of Business and Entrepreneurship Research, 2025)
This study examines the effect of social media use intensity and the quality of content received on self-confidence and its contribution to entrepreneurial intention in the higher education context. A quantitative research design was employed using a survey method, with a questionnaire distributed to 93 respondents selected through proportional random sampling. The study focuses on how social media exposure and the perceived quality of online content may shape students’ confidence in their ability to engage in entrepreneurial activities and develop entrepreneurial intention. The proposed model positions self-confidence as an important psychological factor that can strengthen the relationship between digital media exposure and entrepreneurial intention. The study is expected to provide insights for educators and academic institutions in designing learning support and digital literacy strategies that encourage students to use social media more productively for entrepreneurial development. It also emphasizes the importance of directing students not only toward understanding business concepts but also toward building confidence, initiative, and capability to start and sustain business activities.